A Population-Based Systematic Clinical Analysis With a Single-Center Case Series of Patients With Pulmonary Large Cell Neuroendocrine Carcinoma - Sun, Xu; Wu, Yijun; Shen, Jing; Han, Chang; Kang, Kai; Liu, Zhikai; Zhang, Fuquan (Frontiers in Endocrinology, 2021)
Background and objectives: This study aims to conduct an updated systematic analysis of patients with pulmonary large cell neuroendocrine carcinoma (PLCNC) in the past decades, which concerns incidence and mortality trend, demographics, treatment options, survival and death causes. Methods: Patients who diagnosed with PLCNC at the Peking Union Medical College Hospital (PUMCH) between 2000 to 2020 were retrospectively analyzed. Besides, the population-based Surveillance, Epidemiology, and End Results (SEER) database was also retrieved. Frequencies and average annual age-adjusted rates (AAR) of PLCNC patients were calculated and analyzed by Joint-point regression. Univariate and multivariate Cox regression were used for identifying prognostic factors. Predictive nomograms for overall survival (OS) and cancer-specific survival (CSS) were developed and then validated by calculating C-index values and drawing calibration curves. Survival curves were plotted using Kaplan-Meier method and compared by log-rank test. Causes of death were also analyzed by time latency. Results: A total of 56 PLCNC patients of the PUMCH cohort were included. Additionally, the PLCNC patients in the SEER database were also identified from different subsets. The AAR from 2001 to 2017 were 3.21 (95%CI: 3.12-3.30) per million. The trends of incidence and mortality rates in PLCNC patients has increased at first but seemed to decline in recent years. Beside TNM stage and treatments, older age and male gender were independently associated with poorer survival, while marital status only affected CSS other than OS. The nomograms for OS and CSS presented great predictive ability and calibration performance. Surgery gave significantly more survival benefits to PLCNC patients, and chemotherapy might add survival benefits to stage II-IV. However, radiation therapy seemed to only improve stage III patients’ survival. Conclusions: This study supported some previous studies above incidence, survival and treatment options. The mortality rates seemed to decline recently after an increase at first. Among PLCNC patients, most of deaths occurred within first five years, while other non-PLCNC diseases became more after that. Thus, careful management and follow-up of other comorbidities were of equal importance. Our study may partly solve the dilemma of this PLCNC’s rarity and inspire more insights in future researches.